DAMPAK PENGGUNAAN KECERDASAN BUATAN (AI) TERHADAP PENGAJARAN BAHASA INGGRIS DI POLITEKNIK NEGERI BENGKALIS - Diah Paramita Sari; Fanalisa Elfa (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This study investigates the impact of Artificial Intelligence (AI) on students’ understanding of English learning materials in a vocational higher education context. The main problem addressed is the uncertainty regarding whether AI enhances or The aim is to identify changes in students’ cognitive, affective and behavioral aspects since the integration of AI in the learning process. A qualitative approach was employed through semi-structured interviews with eight English lecturers. The results reveal varied perspectives. In cognitive aspects, AI enhancing access to resources and improving comprehension while risking over-reliance that may weaken students’ critical thinking. More over Overall, the affective aspect indicates that the use of AI in English language learning fosters enthusiasm, interest, and confidence, particularly in writing, but it may also reduce intrinsic motivation and learning interest due to the ease of access that encourages dependence and shortcut use. Overall, the behavioral aspect shows that while AI use improves task punctuality and can support independent learning when applied proportionally, it often reduces active engagement, initiative, and deep learning effort due to students’ reliance on instant answers. The findings suggest that balanced guidance is